2008
DOI: 10.1104/pp.108.123869
|View full text |Cite
|
Sign up to set email alerts
|

Geminivirus-Mediated Gene Silencing fromCotton Leaf Crumple VirusIs Enhanced by Low Temperature in Cotton  

Abstract: A silencing vector for cotton (Gossypium hirsutum) was developed from the geminivirus Cotton leaf crumple virus (CLCrV). The CLCrV coat protein gene was replaced by up to 500 bp of DNA homologous to one of two endogenous genes, the magnesium chelatase subunit I gene (ChlI) or the phytoene desaturase gene (PDS). Cotyledons of cotton cultivar 'Deltapine 5415' bombarded with the modified viral vectors manifested chlorosis due to silencing of either ChlI or PDS in approximately 70% of inoculated plants after 2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 58 publications
3
123
1
4
Order By: Relevance
“…This severely limited the potential for the conventional BSMV-VIGS assay to analyze drought related candidate genes. It was reported that lower temperatures can lead to better silencing phenotypes and targeted gene silencing [32,[35][36][37]. Compared with the experimental condition of our previous BSMV-VIGS study [23], we found that by adjusting greenhouse temperatures from 24 ±1°C to 22 ±1°C, the time period for efficient BSMV-VIGS can be maintained to at least 40 days after inoculation.…”
Section: The Prolonged Vigs Obtained By Lower Temperature and High Humentioning
confidence: 74%
“…This severely limited the potential for the conventional BSMV-VIGS assay to analyze drought related candidate genes. It was reported that lower temperatures can lead to better silencing phenotypes and targeted gene silencing [32,[35][36][37]. Compared with the experimental condition of our previous BSMV-VIGS study [23], we found that by adjusting greenhouse temperatures from 24 ±1°C to 22 ±1°C, the time period for efficient BSMV-VIGS can be maintained to at least 40 days after inoculation.…”
Section: The Prolonged Vigs Obtained By Lower Temperature and High Humentioning
confidence: 74%
“…By contrast, low temperatures often induce a rapid spread of virus diseases by the control of small interfering RNA (siRNA) generation (Szittya et al, 2003). For example, a growth temperature lower than 22 °C is required for efficient TRV-induced gene silencing in tomato, and endogenous gene silencing in cotton is more efficient by Cotton leaf crumple virus (CLCrV) at a relatively cool temperature (22/18 °C) for cotton growth (Liu et al, 2002b;Tuttle et al, 2008). We found that gene silencing based on 2mDNA1 and TbCSV can work in a wide range of temperatures, and no difference in silencing efficiency was observed between 18-32 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Alphasatellites make no significant contribution to the pathogenicity of begomovirus, but most betasatellites are essential for begomovirus to induce typical disease symptoms in the host from which they were isolated (Cui et al, 2004;Wu and Zhou, 2005;Briddon and Stanley, 2006). Begomoviruses and their associated satellite molecules have been successfully modified into VIGS vectors which induce efficient gene silencing in diverse plant species such as Solanum lycopersicum, Nicotiana benthamiana, Arabidopsis thaliana, Manihot esculenta, and Gossypium hirsutum (Carrillo-Tripp et al, 2006;Tuttle et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of fluorescent light in the growth incubator was weaker in the former experiment, which could explain the longer duration. Growth conditions such as light and temperature promote good viral spread and effective silencing (Burch-Smith et al 2004Senthil-Kumar and Mysore 2011a;Tuttle et al 2008).…”
Section: Discussionmentioning
confidence: 99%